Flow cytometry identification of nonhemopoietic neoplasms during routine immunophenotyping. (27th November 2018) - Stacchini, Alessandra; Aliberti, Sabrina; Demurtas, Anna; Maletta, Francesca; Molinaro, Luca; Godio, Laura; Papotti, Mauro
Abstract: Introduction: Nonhemopoietic neoplasms (NHNs) may be encountered during routine flow cytometry (FC) immunophenotyping. The clue of their presence mainly relies on detection of CD45‐negative (CD45−) cells with altered scatter parameters. Methods: In this study, we evaluated a monoclonal antibody combination conceived to characterize the CD45− population by FC, suspected of belonging to NHNs, when present. The panel included CD45 for leucocytes identification, CD326 (clones BerEP4 and HEA‐125) to mark epithelial cells, CD33 to identify myeloid cells, CD138 to trace plasma cells and CD56 useful in the identification of neuroendocrine tumours. 7AAD vital dye was used to gate out dead cells. Results were correlated with cytomorphology and confirmed by histological data, if available. Results: Among 9422 specimens submitted for routine FC investigation, 47 samples that included fine‐needle aspirates, bone marrow aspirates, tissue biopsies and body fluids had a detectable CD45− population and a sufficient cell amount to be further investigated. FC revealed the presence of CD326‐positive epithelial cells in 38 specimens; altered scatter parameters and variable reactivity to the other antigens tested allowed to suspect NHNs in the remaining nine samples. The presence of NHNs was confirmed in all cases by morphology. Conclusions: The current results show that when CD45− cells with altered scatter parameters were detected, cytometrists involved in leukaemia/lymphoma diagnosis may require further FC investigations to rapidly identify NHNs in different specimens, thus reducing the time of the immunohistochemical diagnostic workup to reach a final diagnosis.